Primary cutaneous follicle center lymphoma simulating basal-cell carcinoma on the nasal ala - Wanczinsnki, Mariana Isis (An Bras Dermatol, 2015)
Primary cutaneous B-cell lymphomas (PCBCLs) constitute 25% of all primary cutaneous lymphomas. They present in the skin with no evidence of systemic or extracutaneous disease at the time of diagnosis, after adequate staging. Primary cutaneous B-cell lymphomas differ significantly from their nodal counterparts in relation to both clinical behavior and prognosis. The distinction between primary and secondary B-cell lymphomas is essential for defining prognosis/course of action. Such distinction is also very difficult to make, since primary and secondary B-cell lymphomas are clinically and histologically indistinguishable. We report the case of a patient with primary cutaneous follicle center lymphoma who underwent surgical excision.